Determination of biochemical changes in the blood and lymph after poisoning zinc salts animals (Experimental biology, 2020)
This article studies the cellular and biochemical parameters of rat lymph after exposure to zinc sulfate. It was found that an increase in hemoglobin concentration by 12.61% after administration of zinc salts is an indicator of the development of relative erythrocytosis and chronic hypoxia. After the administration of zinc salts in rats, there is an increase in osmotic pressure in the lymph, as well as the overall level of proteins in the lymph is reduced by 19%. Zinc salts also reduce proteolytic activity in lymph, proteins, lymph nodes, liver, intestinal wall. The decrease in the total amount of protein after poisoning by 32.03% informs about the decrease in protein transportation to the blood system and lymphatic system, as well as about the decrease in the activity of reduction of lymphatic vessels and nodes. As a result of biochemical studies, it was found that lymph is subject to changes in cellular and biochemical parameters that accumulate in individual organs and cause significant changes in the function of a single organism. In case of poisoning, there was an increase in the content of alkaline phosphotase to 22-65%, as well as an increase in the level of aminotransferase enzymes, which indicates a violation of liver function, an increase in liver cytological processes, a decrease in protein synthesis and a violation of metabolic transport. After poisoning rats with zinc salts, there is an increase in the size of the cervical and spotty lymph nodes. There is a slowdown of the lymphatic channel in the lymphatic vessels, a decrease after poisoning by 21.2%. The data obtained made it possible to form a set of data on the negative impact of zinc salts on the body and can serve as a scientific basis for the solution.Keywords: hemoglobin, rats, lymph, lymphatic flow, zinc sulfate, erythrocyte.